STROKE AFTER ELECTRICAL INJURY : CASE REPORT - Eko Arisetijono; Catur Ari Setianto; Sri Budi Rianawati; Masruroh Rahayu; Rodhiyan Rakhmatiar (Journal of Pain, Headache and Vertigo, 2020)
Electrical injury ranging widely reported caused variety of clinical manifestations including brain. Cerebral infarction is one of the manifestation either after low or high voltage electrical injury. We report the case of 49 – year old male who suffered a household electrical injury (110 – 220 Volt) while he was installing the light bulb. He found unconsciousness with left hemiparesis and also central paresis of the left facial nerve (Cranial Nerve VII). The Head Computed Tomography Scan (CT scan) showed wide infarction at right hemisphere which the territory of right cerebral media artery which can be caused by electrical injury.